Baseline and 1-year magnetic resonance imaging of the sacroiliac joint and lumbar spine in very early inflammatory back pain. Relationship between symptoms, HLA-B27 and disease extent and persistence. Issue 11 (19th November 2008) - Marzo-Ortega, H; McGonagle, D; O'Connor, P; Hensor, E M A; Bennett, A N; Green, M J; Emery, P
Abstract : Background: The precise anatomical location of pathology associated with inflammatory back pain (IBP) in early spondyloarthropathy (SpA) remains unclear. Objective: To use MRI to study the sacroiliac joint (SIJ) and lumbar spine (LS) and explore the relationship between sites and extent of inflammation and HLA-B27 status over 12 months. Methods: 54 patients with IBP; median duration 24 weeks (54% HLA-B27 positive; median Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) 5.65) and 22 control subjects (11 with mechanical back pain; 11 volunteers) were recruited and 63% (n = 34) were reassessed at 1 year. Fat saturation and T1-weighted MRI was performed with images being scored for active bone marrow oedema (BMO) lesions representative of inflammation. Results: At baseline 46/54 (85%) patients had BMO (SIJs and LS) compared with 40% in the control group. The majority of affected patients had inflammation at the SIJ level (96% (n = 44); 23.5% (n = 12) LS) and 28.3% (n = 13) at both sites simultaneously. The SIJ activity score confirmed more severe inflammation (BMO grade 2 or 3: 52.2%) in the IBP group (controls = BMO grade 1: 100%; p<0.001). HLA-B27 was associated with both the severity (p = 0.009) and number of baseline SIJ lesions (p = 0.045) and with persistence (SIJ or LS) at 1 year (p = 0.02). 90% of reattenders fulfilled European Spondyloarthropathy Study Group criteria; 73.5% showed MRI inflammation despite clinical improvement (median BASDAI 5.65 to 3.05; p<0.009). Conclusion: LS and SIJ involvement may occur simultaneously in very early SpA and may be differentiated from non-inflammatory back pain by the severity of MRI lesions. HLA-B27 is associated with both the severity of osteitis and its persistence.